ANALISIS HASIL PENGUJIAN ALAT DESTILASI MINYAK SEREH DENGAN KAPASITAS 10 KG - Putrawan, Pajar; Yudisworo, W. Djoko; Lazuardi, Dedi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Lemongrass is one type of essential oil plant, which is considered to have developed. From the distillation of its leaves, lemongrass oil is obtained which is known in the world of trade as Citronella Oil. Currently, the development of essential oils is a major concern for the Indonesian government. Of the various raw materials for making Essential Oils, one of the essential oil raw materials in Indonesia that is good to be developed is Lemongrass. The purpose of this study was to obtain essential oils through the Extraction and Distillation process, obtaining Yield percentage and Water Content. Based on the results of the test and observation, the essential oil produced has physical and chemical characteristics that are in accordance with the requirements. The characteristics of lemongrass essential oil produce essential oils with a specific gravity of 0.86 mg/L.